Driftwood cottage [compact disc, unabridged] - Woods, Sherryl (Woods, Sherryl. Chesapeake Shores novel., 2011)
Single mom Heather Donovan's dreams of home and family are seemingly within reach when she settles in Chesapeake Shores. The welcoming arms of the boisterous, loving O'Brien clan embrace her and her son. But accepting their support seems to further alienate her son's father, Connor O'Brien. His parents' divorce and his career as a divorce attorney have left him jaded about marriage. Then everything changes. Will the possibility of a future without Heather make Connor look at love differently?